HOST MORTALITY, LETHAL PERIOD, TRANSMISSIBILITY, AND THRESHOLD DENSITY OF VERTICILLIUM LECANII – SCOTINOPHARA SP. MYCOSIS - F.X. Susilo, Nyoman Mulyasari, Rozali,; Sudi Pramono . (Universitas Lampung, 2005)
Host mortality, lethal period, transmissibility, and threshold density of Verticillium lecanii – Scotinophara sp. mycosis. This study, conducted at Laboratory of Plant Protection Gading Rejo, Tanggamus-Lampung during March – October 2002, was aimed at determining the host mortality, lethal period, transmissibility, and threshold density of Verticillium lecanii – Scotinophara sp. mycosis generated from cadaver exposure and conidial spray in potted rice plants. The cadaver exposure was implemented by inoculating various levels of inoculum to different levels of host population while the conidial spray was done by spraying V. lecanii starter suspension or suspension of homogenized Scotinophara sp. cadavers to the host. After incubation, newly formed cadavers (new infections) were collected. The host mortality was expressed as percentage of the host number by inoculation technique while the lethal (infection) period was averaged from overall data (grand average) or from data sorted by inoculation technique. Transmissibility was taken to be the significant regression slope between new infections and potential contact while threshold density value was taken as the ratio between the inverse value of lethal period (numerator) and transmissibility (denominator). Results showed that the host mortality after exposure to 2 cadavers was significantly lower (1.7%) than that after exposures to 4 – 10 cadavers or after conidial sprays (10 – 25% range). The lethal period of the mycosis ranged from 5.2 to 15.8 days (no difference between inoculation techniques) while the disease transmissibility was 0.025 infection potential contact-1. The threshold density of the mycosis was 4.0 individuals of susceptible Scotinophara sp. rice plant-1. The fungus V. lecanii could be importance as a naturally-occurring biological control agent against Scotinophara sp.